2005
DOI: 10.1111/j.1600-6143.2004.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic Live Donor Nephrectomy (RPLDN): Establishment and Initial Experience of RPLDN at a Single Center

Abstract: We tried to establish the technique of retroperitoneoscopic live donor nephrectomy (RPLDN).Between July 2001 and March 2004, 135 renal transplant donors underwent RPLDN. Low (average: 7 mmHg) CO 2 gas pressure was employed during the procedure. All procedures were performed through a three-port retroperitoneal approach without opening the peritoneal cavity. The hand-assisted technique was not used. One hundred and twenty-seven cases were of left and eight cases were of right nephrectomy. Donor nephrectomy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
(38 reference statements)
0
29
1
1
Order By: Relevance
“…Today, most surgeons use the transperitoneal approach, except few clinics who established primarily the retroperitoneoscopic approach [19][20][21][22]. Although the limited working space makes the retroperitoneoscopic approach more demanding compared to the transperitoneal approach, it oVers two major advantages: Wrst, it is possible to operate without interfering with intraperitoneal organs or adhesions in case of prior abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Today, most surgeons use the transperitoneal approach, except few clinics who established primarily the retroperitoneoscopic approach [19][20][21][22]. Although the limited working space makes the retroperitoneoscopic approach more demanding compared to the transperitoneal approach, it oVers two major advantages: Wrst, it is possible to operate without interfering with intraperitoneal organs or adhesions in case of prior abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the same surgeon performs the donor and recipient operation may remove some stress, as the length of the renal graft vessels becomes less of a potential issue. In our series, as in the report by Tanabe et al, [10] the surgical time was defined as the time from the first port insertion until removal of the kidney. The mean surgical time in our series was shorter than in the study of Tanabe et al, [10] similar to that reported by Bachmann et al [8] and slightly longer than that reported by Ma et al [9] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In our series, as in the report by Tanabe et al, [10] the surgical time was defined as the time from the first port insertion until removal of the kidney. The mean surgical time in our series was shorter than in the study of Tanabe et al, [10] similar to that reported by Bachmann et al [8] and slightly longer than that reported by Ma et al [9] (Table 3). In our series the proportion of rightsided nephrectomies was considerably higher than in the compared series (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure's history has been dominated by reports of the benefits of this less invasive procedure for the donor (3)(4)(5)(6)(7) and on organ supply (8)(9)(10)(11)(12) and of excellent recipient renal outcomes (36), and some other groups have also found worse early allograft function in laparoscopically procured allografts (13,(37)(38)(39)(40)(41)(42)(43)(44) (45). Additionally, animal and human studies have shown that the pneumoperitoneum used during the lapNx procedure impairs renal cortical blood flow (45)(46)(47)(48)(49)(50) (52)(53)(54)(55)(56) or slow graft function (SGF) (53) (57)(58)(59)(60) (53)(54)(55)(56) Ratner (12) and by Derweesh (69) and national data from the era prior to the laparoscopic nephrectomy (70) …”
Section: Introductionmentioning
confidence: 99%